A prediction method of the effective volume in sediment-filled salt cavern. (10th December 2022) - Liang, Xiaopeng; Ma, Hongling; Li, Peng; Cai, Rui; Zhao, Kai; Li, Hang; Yu, Haibing; Yang, Chunhe
Abstract: An emerging trend in China is to build gas storage in salt rock formations with a large number of interlayers. However, the sediments formed after the collapse of the interlayers may occupy >80 % of the volume of the salt cavern. The effective volume of salt cavern cannot be investigated by sonar in such cavities. Therefore, a method to predict the effective volume in sediment-filled salt cavern is proposed based on a liquid injection test. First, the bulk modulus of brine and the salt cavern compressibility factor were used to characterize the brine compression and the salt cavern expansion during liquid injection. The volume equilibrium relationship for the liquid injection test was derived. Second, a liquid injection test was conducted for a salt cavern in China. The compressibility factor of this salt cavern is calculated based on the prediction method of the cavern morphology proposed in this paper. The effective volume of the salt cavern is derived. The method was validated by numerical simulation, and the deviation between the two was 0.79 %. For the construction of salt cavern gas storage, this method has the significance of guidance and reference. Highlights: We propose a new method to predict the effective volume of sediment-filled salt cavern. Cavern compressibility factor and bulk modulus of brine are utilized in the method. The relationship between cavern compressibility factor and salt cavern volume was obtained. A water injection test of a salt cavern was carried out. This method produced satisfactory results for predicting the effective volume of a sediment-filled salt cavern.